Knock-down of oncohistone H3F3A-G34W counteracts the neoplastic phenotype of giant cell tumor of bone derived stromal cells. (28th April 2019) - Fellenberg, J.; Sähr, H.; Mancarella, D.; Plass, C.; Lindroth, A.M.; Westhauser, F.; Lehner, B.; Ewerbeck, V.
Abstract: Giant cell tumors of bone (GCTB) are semi-malignant tumors associated with extensive osteolytic defects and massive bone destructions. They display a locally aggressive behavior and a very high recurrence rate. Recently, a single mutation has been identified in GCTB affecting the H3F3A gene coding for the histone variant H3.3 (H3.3-G34W). The aim of this study was to investigate whether H3.3-G34W is sufficient to drive tumorigenesis in GCTB. Initially, we confirmed the high frequency of this mutation in 94% of 84 analyzed tissue samples. Using a siRNA based approach we could selectively knockdown H3.3-G34W in primary neoplastic stromal cells isolated from tumor tissue (GCTSC). H3.3-G34W knockdown caused a significant inhibition of cell proliferation, migration and colony formation capacity in vitro . Xenotransplantation of GCTSCs onto the chorioallantoic membrane of fertilized chicken eggs further demonstrated a significant impact of H3.3-G34W knockdown on tumor engraftment and growth in vivo . Our data indicate that H3.3-G34W is sufficient to drive tumorigenesis in GCTB. Apart from the application of H3.3-G34W screening as diagnostic tool, our data suggest that H3.3-G4W represents a promising target for the development of new GCTB therapies. Highlights: Oncohistone H3.3-G34W is present in ≥ 94% of GCTBs. H3.3-G34W can selectively be knocked down by siRNA. H3.3-G34W knockdown reduces proliferation, migration and colony formation in vitro . H3.3-G34W knockdown inhibits tumor formation and growth in vivo . H3.3-G34W drives tumorigenesis in GCTB.